Metachronous Isolated Contralateral Lung Metastasis from Pulmonary Adenosquamous Carcinoma with EGFR Mutation - Kawai, Hitomi; Iguchi, Kesato; Takayashiki, Norio; Okauchi, Shinichiro; Satoh, Hiroaki (Acta medica (Hradec Kralove), 2020)
Lung metastasis and metachronous double primary lung cancer are both common and often present diagnostic challenges. We present a case of metachronous isolated contralateral lung metastasis from pulmonary adenosquamous carcinoma with EGFR mutation. A 75-yearold woman presented with left lung nodule on a routine follow-up chest radiograph. She had had surgery for pulmonary adenocarcinoma with EGFR Ex21 L858R mutation 6 years ago. She underwent surgical resection, and histologic findings revealed adenosquamous carcinoma with the same EGFR mutation. Re-assessment of the resected specimen of the primary tumor resected 6 years ago revealed the morphologically similarity to the left lung tumor. Based on morphological and genetic identity, final diagnosis was adenosquamous cell carcinoma and metachronous isolated contralateral lung metastasis. The diagnosis of metachronous isolated metastasis is difficult but important for appropriate management and prediction of prognosis. A careful pathological examination and evaluation of genetic abnormality are needed to make the correct diagnosis.
Keywords: adenoskvamózní karcinom; nádory plic; Pneumonectomy; Patient Care Management; Lung Neoplasms; Humans; diferenciální diagnóza; ErbB Receptors; Female; mutace; Aged; EGFR mutation; Neoplasms, Second Primary; Diagnosis, Differential; senioři; lidé; lung adenosquamous carcinoma; Carcinoma, Adenosquamous; erbB receptory; pneumektomie; sekundární malignity; Neoplasm Metastasis; metastázy nádorů; ženské pohlaví; recurrence; Mutation; management péče o pacienta